From Attachment Insecurity to Trauma Expression: A Professional Exploration of Mental Health Consequences - Shahid, Areeja; Ali, Saima Massom (Annals of Human and Social Sciences, 2024)
This study aims to investigate the potential link between insecure attachment styles and Trauma symptoms. Specifically anxiety, depression, and sexual abuse trauma. Attachment theory describes the emotional bond of safety and comfort between a child and the caregiver. However, if that bond is ruptured the child develops an insecure attachment that leads to negative mental health consequences. A sample of female participants was recruited from various universities and wellness centers. The Adult Attachment Scale and Trauma Symptom Scale were administered to the participants. 50 females who scored high on the anxious attachment scale underwent further analysis using the trauma symptom scale. The findings indicated a significant correlation between anxious attachment and heightened levels of anxiety 0.539 (ρ=.03, P<.05), depression 0.339 (ρ=.04, P<.05), and no relationship with sexual abuse trauma -0.014 (ρ=.03, P<.05). This study empirically supports the hypothesis that insecure attachment styles contribute significantly to Trauma Symptoms. These findings contribute to the existing body of knowledge, emphasizing the need for targeted interventions addressing insecure attachment styles to lessen the risk of Trauma Symptoms.